A survey of the hearing impaired children regarding scholastic achievements in normal schools - Asok Kumar S (Journal of All India Institute of Speech and Hearing, 1970)
The education of the aurally handicapped has been among the earliest of the Special Educational problems to receive organized attention. Still systematic research is needed in the field and this has been frequently mentioned by the pioneers in this field. Also approaches in the education of the aurally handicapped change from day to day.